Apnoea monitors compared with weighing scales for siblings after cot death. Issue 11 (November 1985) - Emery, J L; Waite, A J; Carpenter, R G; Limerick, S R; Blake, D
Abstract : A randomised control trial was carried out on support measures given to parents with a subsequent child after previously suffering a cot death. Apnoea monitors were used in one group and weighing scales in the other. General support measures given to both groups included the keeping of symptom charts and weekly visits by health visitors. Many alarms occurred which were presumed to be false. Eleven per cent fewer symptoms were reported by parents of children on monitors than parents of children being weighed daily. Both systems were acceptable and gave parents confidence. Sixty per cent of parents were reluctant to give up using the monitor compared with 26% of parents using scales. Virtually all parents commented on the great value of the weekly home visit of the health visitor and the symptom diary.